2009
DOI: 10.21432/t24881
|View full text |Cite
|
Sign up to set email alerts
|

How Research Moves into Practice: A Preliminary Study of What Training Professionals Read, Hear, and Perceive

Abstract: In the growing body of research on the practice of training and development, several studies suggest that use of research-based findings in practice is low. The present study was designed to better understand the research-practice gap by exploring these questions: (1) Which published sources in the field are practicing professionals reading? How frequently do they read these materials? (2) Which conferences and meetings do practicing professionals attend? How frequently do they attend these events? (3) In what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Современная западная модель образования начинала складываться с конструктивизма, поместившего в центр образовательного процесса не учителя, а ученика, который получает знания, размышляя над собственным опытом [14]. Знания в конструктивизме -это сформированные убеждения на основе знания социального мира и культуры общества, т.е.…”
Section: обсуждение результатов (теория современного (смешанного или ...unclassified
“…Современная западная модель образования начинала складываться с конструктивизма, поместившего в центр образовательного процесса не учителя, а ученика, который получает знания, размышляя над собственным опытом [14]. Знания в конструктивизме -это сформированные убеждения на основе знания социального мира и культуры общества, т.е.…”
Section: обсуждение результатов (теория современного (смешанного или ...unclassified
“…Мысалы, Платон білім беруді -оқушының оқып үйренетін табиғи қабілеттеріне негізделген және кез келген адамның қолы жетпейтін ізгілік пен шындық туралы білім алу жүйесі деп есептеген (19 Нәтижелерді талқылау. Қазіргі заманғы батыстың білім беру үлгісі білім беру үдерісінің орталығына мұғалімді емес, жеке тәжірибесін талқылап, ой бөлісуші білім алатын оқушыны қоя отырып, конструктивизм негізінде қалыптаса бастады (14). Конструктивизмдегі білім -қоғамның әлеуметтік әлемі мен мәдениетін ұғыну негізінде қалыптасқан сенім, яғни оқыту теориясы бұл ретте білімнің әлеуметтік құрылымы болып саналады.…”
Section: цифрлық білім беруді білім алушылардың интеллекті мен ұлттық бірегейлігі негізінде жаңғырту туралыunclassified
“…In both of those fields, researchers have attempted to empirically explore the extent to which research from academe moves into practice. For example, Lysenko [8] and Carliner et al [9] have explored the extent to which practicing professionals read the research literature. Both have found that, although practicing professionals have an interest in research, few actually regularly read research publications.…”
Section: Literature Reviewmentioning
confidence: 99%